Automated assembly scaffolding using RagTag elevates a new tomato system for high-throughput genome editing - Michael Alonge; Ludivine Lebeigle; Melanie Kirsche; Katie Jenike; Shujun Ou; Sergey Aganezov; Xingang Wang; Zachary B. Lippman; Michael C. Schatz; Sebastian Soyk (Genome Biology, 2022)
Abstract Advancing crop genomics requires efficient genetic systems enabled by high-quality personalized genome assemblies. Here, we introduce RagTag, a toolset for automating assembly scaffolding and patching, and we establish chromosome-scale reference genomes for the widely used tomato genotype M82 along with Sweet-100, a new rapid-cycling genotype that we developed to accelerate functional genomics and genome editing in tomato. This work outlines strategies to rapidly expand genetic systems and genomic resources in other plant species.